(untitled) (Fiep Bulletin - online, 2026)
Introduction: The text consists of an excerpt from a research carried out in the Professional Master’s Program in Physical Education in the National Network - ProEF/UESPI, in the years 2023-2024, which had as its guiding theme High School Reform, promoted by Law No. 13,415/2017. Objective: To analyze the transformations undergone by the Physical Education discipline in the process of implementing the New High School from the teaching perspective of two teachers working in High School at a state school in the municipality of Wall Ferraz-PI. Methods: It was characterized as a descriptive and analytical qualitative approach (Documentary Analysis and Life History Method) with Interpretive Analysis of the data. Results: School Physical Education was impacted by the loss of space in the New High School in Piauí, accentuating its invisibility and becoming hostage to the hierarchy of knowledge. Conclusion: The diversification and redefinition of pedagogical practices in Physical Education are essential for its survival as a curricular component of the new High School architecture.